Combined Effects of ICAM-1 Single-Nucleotide Polymorphisms and Environmental Carcinogens on Oral Cancer Susceptibility and Clinicopathologic Development - Lin, Chiao-Wen (Public Library of Science, 2013)
BACKGROUND: In Taiwan, oral cancer has causally been associated with environmental carcinogens. Intercellular adhesion molecule (ICAM)-1, a cell adhesion molecule with a key role in inflammation and immunosurveillance, was implicated in carcinogenesis by facilitating instability in the tumor environment. The current study explored the combined effect of ICAM-1 gene polymorphisms and exposure to environmental carcinogens on the susceptibility of developing oral squamous cell carcinoma (OSCC) and the clinicopathological characteristics of the tumors. METHODOLOGY AND PRINCIPAL FINDINGS: Four single-nucleotide polymorphisms (SNPs) of the ICAM-1 gene from 595 patients with oral cancer and 561 non-cancer controls were analyzed by a real-time PCR. We found that the ICAM-1 rs5498 polymorphism and the TAGG or TACG haplotype of 4 ICAM-1 SNPs (rs3093030, rs5491, rs281432, and rs5498) combined were associated with oral-cancer susceptibility. Among 727 smokers, ICAM-1 polymorphisms carriers with the betel-nut chewing habit had a 27.49–36.23-fold greater risk of having oral cancer compared to ICAM-1 wild-type (WT) carriers without the betel-nut chewing habit. Among 549 betel-nut chewers, ICAM-1 polymorphisms carriers who smoked had a 9.93–14.27-fold greater risk of having oral cancer compared to those who carried the WT but did not smoke. Finally, patients with oral cancer who had at least 1 T allele of ICAM-1 rs5491 or 1 G allele of rs281432 were at lower risk of developing an advanced clinical stage (III/IV) (p<0.05), compared to those patients with AA or CC homozygotes. CONCLUSIONS: Our results suggest that the ICAM-1 rs5498 SNP and either of 2 haplotypes of 4 SNPs combined have potential predictive significance in oral carcinogenesis. Gene-environment interactions of ICAM-1 polymorphisms, smoking, and betel-nut chewing might alter oral-cancer susceptibility. ICAM-1 rs5491 and rs281432 may be applied as factors to predict the clinical stage in OSCC patients.